Objective Analyses of Reported Real-Time Audio Instrumental Transcommunication and Matched Control Sessions: A Pilot Study - Boccuzzi, Mark; Beischel, Julie (Journal of Scientific Exploration, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif]-->This study asked: Can the presence of instrumental transcommunication (ITC) be objectively detected in sessions collected by an experienced operator using EVPMaker software producing a random stream of allophones (short speech elements)? Several aspects of ten Active Sessions were examined: (1) the distribution of the allophones generated; (2) independent, blinded listening panel interpretations of session samples; (3) content analysis of questions posed by the operator and her perceived responses; and (4) automated interpretation of session samples using speech recognition software (SRS). For analyses (1) and (2), 10 ITC-free Control Sessions collected by the investigators were used for comparison, and it was determined that no differences existed between the Active and Control Sessions regarding: (a) the allophones present and (b) the proportions of participants who recognized words in the samples. Analysis (3) revealed that the responses perceived by the operator did not consistently contain information that logically matched her questions, and analysis (4) demonstrated that SRS was unable to detect the phrases perceived by the operator. Future studies may wish to focus on the psychology and motivation of ITC operators; the impact of the perceived communication; and the potentially psi-conducive effects of using EVPMaker to acquire veridical information. Keywords: electronic voice phenomena—instrumental transcommunication—EVP—ITC—speech recognition software—listening panel